Too Tired to Lean In? Sleep Quality Impacts Women's Daily Intentions to Pursue Workplace Status. - Sheppard, Leah D.; Loi, Teng Iat; Kmec, Julie A. (Sex Roles, 2022)
An assumption of sleep and self-regulation theories is that sleep quality impacts mood which, in turn, prompts individuals to revise their work-related goals. We propose that gender differences in emotion, emotional regulation, and career aspirations layer complexity onto these basic assumptions. In the current work, we investigate the effect of daily sleep quality – via positive affect – on intentions to pursue more status and responsibility at work (i.e., aspirations), as a function of participant gender. We test our model using experience sampling methodology, surveying 135 full-time employees residing in the United States twice daily across two consecutive work weeks (10 workdays), for a total of 2,272 observations. We find that among women, but not men, sleep quality is positively related to positive affect which, in turn, relates to greater daily intentions to pursue more status and responsibility at work. We discuss the implications of our work for research and practice.